Hubungan Pola Makan dengan Kejadia Gastroesophageal Reflux Disease (Gerd) pada Mahasiswa Keperawatan Unika Santu Paulus Ruteng - Kornelia Romana Iwa; Saverius Mahu (Universitas Malahayati Lampung, 2026)
ABSTRACT Gastroesophageal Reflux Disease (GERD) is a health problem that often occurs in productive ages, including students,and can interfere with activities and reduce quality of life. One of the factors that influence the occurrence of GERD is an unhealthy diet, such as skipping meals, consuming spicy, sour, or fatty foods in excess. Purpose: to determine